Bionomik Nyamuk Anopheles spp di Desa Sumare dan Desa Tapandullu Kecamatan Simboro Kabupaten Mamuju Provinsi Sulawesi Barat Tahun 2011 - Andri Dwi Hernawan; Syarifuddin Hamal (Loka Litbang Kesehatan Pangandaran, 2011)
Abstract. Tapandullu and Sumare Villages are area of malaria high endemic in Mamujudistricts, West Sulawesi province, located in coastal areas. Anopheles mosquitoes in the tworegions are largely unknown, neither species, bionomic density. To find out the fauna andbionomic and dominant Anopheles mosquito, has been conducted a spot survey entomology.Surveys conducted for three consecutive days with the capture of mosquitoes at night anddid a long time outside the home, including around the cattle pen. Catching method is to baitpeople and catching mosquitoes rest. Mosquitoes captured, identified the species, calculateddensity and ovarian surgery performed to calculate the parity rate.From the survey, concluded that chance as a mosquito vector of malaria in both regions arespecies of Anopheles subpictus